A utilização do malaware em investigações criminais em face do estabelecido pelos direitos fundamentais - Junior, Washington Trindade da Silva (2022)
New communication and information technologies and the ubiquity of electronic-digital devices bring profound cultural changes to society and force control bodies to adopt methods for obtaining sources of evidence different from those available until a few years ago, as is the case with malware. The legal system in the Federative Republic of Brazil in 1988, as well as in Portugal, does not contemplate the use of the arbitrary code, and, nevertheless, it appears that this legislative task of regulating the aforementioned tool cannot be neglected indefinitely. Challenges such as the large-scale use of cryptography and the crimes constantly committed on the dark web will inevitably compel these countries to develop a standard that expressly enables the use of the malicious code tool in the course of criminal investigations. Given the diversity of functions that can be activated whenever a computer system is penetrated by malicious code, and the massive amount of data that the control bodies will have during investigations of crimes whenever they make use of this hidden and extrasensory method, the Legislative Power must maintain unsurpassed respect for the legal principles and fundamental rights applicable at the time of erecting a new legal instrument that will regulate the issue. State regulation will observe the expansionist tendency attributed to fundamental rights, as well as the constitutional principles that will bind the decision judicial to similar parameters.